PHONOLOGYCAL AND LEXICAL DIFFERENCES IN PULAU LAYANG, RANTAU ALAY, AND SALAM BUKU VILLAGES (INTERNATIONAL SEMINAR, 2025)
This study investigates the dialectal variations within the Jambi Malay language as spoken in three villages: Pulau Layang, Rantau Alai, and Salam Buku, all located in the Batang Masumai Sub-district of Merangin Regency, Jambi Province. The study utilizes a mixed-methods approach, combining quantitative and qualitative descriptive methods. Data were collected using a Swadesh list consisting of 200 basic vocabularies. The theoretical framework guiding this study is rooted in the field of dialectology The results reveal that the dialects spoken in Pulau Layang, Rantau Alai, and Salam Buku are highly similar overall, suggesting that they likely belong to a single dialect cluster within the Jambi Malay language. However, the data also reveal clear and consistent differences, especially at the phonological and lexical levels, which indicate localized linguistic shifts influenced by geography, social interaction, or historical migration patterns. From the analysis of the 200 vocabulary items: 113 items were identified as cognates, 77 items exhibited phonological differences, 30 items showed lexical differences These findings suggest that while the dialects are mutually intelligible and share a strong common linguistic foundation, there are distinctive features that differentiate one village from another. These features are important markers of regional identity and demonstrate the dynamic nature of language change even within a relatively small geographical area.